2020
DOI: 10.3389/fnmol.2020.00158
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Stress Impairs Postnatal Learning and Memory Development via Disturbance of the cGMP–PKG Pathway and Oxidative Phosphorylation in the Hippocampus of Rats

Abstract: Clinical and animal studies have found that prenatal stress can lead to pathological changes in embryos and fetuses. However, the mechanisms through which this occurs have not been made clear. In the present study, pregnant rats were subjected to chronic psychological stress during gestational days using an improved communication box system, and the changes in behavioral performance and proteins in the hippocampus of offspring were analyzed. It was found that prenatal stress caused postnatal growth retardation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Meanwhile, the KEGG enrichment analysis indicated that the upregulated circRNAs were mainly enriched in the MAPK, cGMP-PKG and Wnt signaling pathways, and the downregulated circRNAs were primarily enriched in the PI3K-Akt, MAPK and AMPK signaling pathways. These signaling pathways have been validated to be closely related to inflammation and apoptosis ( Suo et al, 2018 ; Chen et al, 2019 ; Gabbouj et al, 2019 ; Sun Q. Y. et al, 2019 ; Li et al, 2020 ; Yue and Lopez, 2020 ; Liu X. Y. et al, 2021 ), further indicating that neuroinflammation and apoptosis might play vital roles in the development of cognitive deficits after CCI. Additionally, the miRNAs and targeted genes associated with the typical upregulated and downregulated circRNAs were further identified.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Meanwhile, the KEGG enrichment analysis indicated that the upregulated circRNAs were mainly enriched in the MAPK, cGMP-PKG and Wnt signaling pathways, and the downregulated circRNAs were primarily enriched in the PI3K-Akt, MAPK and AMPK signaling pathways. These signaling pathways have been validated to be closely related to inflammation and apoptosis ( Suo et al, 2018 ; Chen et al, 2019 ; Gabbouj et al, 2019 ; Sun Q. Y. et al, 2019 ; Li et al, 2020 ; Yue and Lopez, 2020 ; Liu X. Y. et al, 2021 ), further indicating that neuroinflammation and apoptosis might play vital roles in the development of cognitive deficits after CCI. Additionally, the miRNAs and targeted genes associated with the typical upregulated and downregulated circRNAs were further identified.…”
Section: Discussionmentioning
confidence: 94%
“…The downregulated circRNAs were mainly enriched in the PI3K-Akt, MAPK, AMPK, and Jak-STAT signaling pathways ( Figure 2E ). Of note, these processes and pathways were reported to be associated with inflammation and apoptosis in the development of cognitive deficits ( Suo et al, 2018 ; Chen et al, 2019 ; Sun Q. Y. et al, 2019 ; Feng et al, 2020 ; Li et al, 2020 ; Liu X. Y. et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the negative effects of PNS on the offspring's learning and memory behavioral deficits, Li and collaborators have recently analyzed the hippocampal protein profiles of offspring whose mothers were exposed to PNS, in terms of chronic fear stress during pregnancy, compared to control animals (Li et al, 2020).…”
Section: Oxidative Stressmentioning
confidence: 99%
“…All mentioned animal models cause memory deficits that differ in severity and memory type affected (for more information on animal models of memory deficits please see Gallagher, 1997 ; Götz and Götz, 2009 ; More et al, 2016 ; van der Staay et al, 2011 ). They may be a result of impaired cholinergic (scopolamine), glutamatergic (dizocilpine, phencyclidine) or serotonergic neurotransmission (para-chlorophenylalanine), neurons death ( β -amyloid(25–35)-peptide, 192 IgG-saporin, trimethyltin, ibotenic acid, carbon monoxide (CO), brain ischemia, olfactory bulbectomy), oxidative stress (cocaine) or oxidative phosphorylation (prenatal stress) (for more information on animal models of cognitive impairments please see Beraki et al, 2009 ; Cheng et al, 2012 ; Deryabina et al, 2020 ; Li et al, 2020 ; Muriach et al, 2010 ; Nakajima et al, 2007 ; Pepeu, 2004 ; van der Staay et al, 2011 ).…”
Section: Memory Functioning and Sigma-1 Receptorsmentioning
confidence: 99%